Intraocular Amphiregulin antibody and axial elongation in nonhuman primates - Wang, Wenyao; Nan, Yan; Huang, Tiejun; Pu, Mingliang; Jonas, Jost B. (Frontiers in Ophthalmology, 2022)
Purpose To examine the effect of intraocularly applied amphiregulin antibody on physiological axial elongation in young nonhuman primates. Methods The experimental study included six male 12-months-old macaque nonhuman primates (body weight:2.46 ± 0.25kg;range:2.20-2.90kg). In the experimental group (n=3 animals), three intravitreal injections of amphiregulin antibody (100μg/50μl) were applied to the left eyes at intervals of 4-6 weeks, and injections of phosphate buffered solution (50μl) were applied to the right eyes. Three other animals were assigned to a blank control group. Results During the study period of 23.6 weeks, axial length in the experimental group did not change in the left eyes (18.91 ± 0.37mm to 18.94 ± 0.67mm;P=0.90), while it linearly increased in the right eyes (18.87 ± 0.38mm to 19.24 ± 0.53mm;P=0.056) and in the control group (left eyes:19.15 ± 0.22mm to 19.48 ± 0.22mm;P=0.009; right eyes:19.17 ± 0.15 mm to 19.46 ± 0.23 mm;P=0.024). The interocular difference in axial elongation increased in the experimental group from -0.11 ± 0.12mm at 4 weeks after baseline to -0.34 ± 0.15mm at the study end, while in the control group, the interocular side difference did not change significantly (from 0.01 ± 0.10 mm to 0.03 ± 0.08 mm;P=0.38). The difference in the interocular difference in axial elongation between the two groups was significant at 8 weeks (P=0.01), 15 weeks (P=0.007), and at study end (P=0.02). The interocular difference in axial length correlated with the interocular difference in vitreous cavity length (standardized regression coefficient beta:0.85;P<0.001). The interocular axial length difference was inversely associated with the interocular refractive error difference (beta:-0.49;P<0.001). Conclusions Intraocularly applied amphiregulin antibody (100μg) reduced the physiological ocular axial elongation in juvenile nonhuman primates.